Cadmium sulfide-based nanomaterials for photocatalytic hydrogen production. Issue 25 (6th June 2018) - Yuan, Yong-Jun; Chen, Daqin; Yu, Zhen-Tao; Zou, Zhi-Gang
Abstract : Recent developments in cadmium sulphide-based photocatalysts including heterojunctions, solid solutions and quantum dots for photocatalytic H2 production are reviewed. Abstract : Solar hydrogen generation via photocatalytic water splitting represents an attractive strategy to address the global energy crisis and environmental pollution issues. CdS-based photocatalysts, including nanosized CdS powder, CdS-based solid solutions and CdS quantum dots, have attracted significant attention for photocatalytic H2 production due to their unique advantages, including strong visible light absorption capacity, suitable band edge levels and excellent electronic charge transfer. This review focuses on recent advances in material design and technological aspects of CdS-based photocatalysts for applications in photocatalytic H2 production. A brief overview of basic concepts and principles of photocatalytic water splitting was given in the Introduction section, followed by the basic properties of CdS. Then, the utilization of three main types of CdS-based semiconductor photocatalysts for solar H2 generation is introduced, and those important factors which can determine the photocatalytic performance were also discussed in detail. Special consideration has been given to the effect of morphology, interfacial junctions, exposing facet and cocatalysts on the photocatalytic performance of CdS-based photocatalysts. Finally, a roadmap of possible future directions to further explore the research field of CdS-based photocatalysts for solar H2 generation is also discussed.